PENGARUH MEKANISME CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN - Ridho Alief Noviawan; Aditya Septiani (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to examine the influence of corporate governance (board of commissioner, independent commissioner, board of director, and audit committee) and ownership structure (institutional ownership and managerial ownership) on financial performance (return on assets). Company’s management should be monitored and controlled to ensure that company management is fit with the regulation so the harmony of interest between management and shareholders will be occured and it also could reduce the conflict of interest.This study uses secondary data from manufacturing companies’ financial report which is listed on Bursa Efek Indonesia in 2007 – 2011. Sampling method of this study is using purposive sampling method. This study uses multiple linear regression as analysis instrument. Before doing the regression test, it’s examined by using classical assumption tests.The results of this study indicate that board of commissioner, independent commissioner, audit committee, and managerial ownership did not influence financial performance while board of director and institutional ownership influenced it. This proves that good relation with the external parties and the ownership from other institutions could increase financial performance.